Penyakit Ain dalam Perspektif Islam: Studi Takhrij dan Syarah Hadis - Laelatul Azqia (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the syarah of hadith related to other diseases from an Islamic perspective. This study uses a qualitative method that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of the research and discussion show that the quality status of the hadith about other diseases is considered authentic based on the takhrij hadith. And the syarah hadith explains that this ain disease is very dangerous for people who are affected by it, therefore the way to cure it is by ruqyah syar'iyyah therapy. The conclusion of this study is that ruqyah syar'iyyah therapy is permissible and has a shari'a basis as well as prayers and remembrance that are used as incantations that can heal people affected by other diseases, trance and the like. Because with this therapy we can protect ourselves through readings or mantras that are read for people affected by the disorder.